Extraordinary optical transmission and enhanced magneto-optical Faraday effects in one-dimensional metallic gratings. (11th November 2020) - Lei, Chengxin; Man, Zhongsheng; Tang, Shaolong
Abstract: The optical and magneto-optical (MO) properties of two different magneto-optic-plasmonic structures including double-layer and single-layer metallic gratings have been investigated. Numerical simulations based on the extended finite difference time domain method have revealed that, in the two proposed structures, apart from the extraordinary optical transmission effect, there arises high MO Faraday rotation in a broad spectrum spanning visible to near-infrared frequencies. Despite the easy fabrication process, the double-layer grating structure still shows an enhancement in transmittance, Faraday rotation, and figure of merit by two, five, and two times, respectively, compared to the single-layer structure, and this can be further improved by suitably modifying the configuration. The physical mechanisms of the physical phenomena are explained in detail.